Gendered dimensions of sustainable land management: Evidences from farm size and training effects on willingness to pay in Ghana’s Volta Region - James Dickson Fiagborlo; Mexoese Nyatuame; Stella Ahone Ntoko (PLoS ONE, 2026)
Land degradation is a critical threat to agricultural productivity in Ghana, reducing soil fertility and deepening rural poverty. Efforts to promote Sustainable Land Management (SLM) have increased, but adoption remains uneven, with persistent gender disparities in access to land, training, and decision-making. This study draws on survey data from 1,036 farming households across five municipalities in Ghana’s Volta Region to examine how SLM training and farm size affect farmers’ willingness to pay (WTP) for SLM practices, with a focus on gender differences. A Tobit regression model is used to estimate both main and interaction effects. The results support the study hypotheses. SLM training (β = 0.164, p < 0.01 ) significantly increases WTP, with stronger effects among male farmers, confirming H1. Farm size (β = 0.058, p < 0.01 ) is positively associated with WTP, as larger landholdings increase farmers’ investment capacity, supporting H2. Gender differences are evident: male farmers show higher baseline WTP, while female farmers show large increases in WTP as access to land and SLM training improves, partially supporting H3 and suggesting that disparities are driven mainly by structural constraints. The three-way interaction between SLM training, gender, and farm size is positive and significant (β = 0.375, p < 0.05 ), confirming H4 and indicating that the effect of SLM training on WTP depends jointly on gender and resource endowment. Overall, the findings suggest that gender is central to understanding investment decisions in SLM and highlight the need for gender-responsive policies that address inequalities in access to land, training, and productive resources.